An Exploratory Study and a Theoretical Hypothesis on the Possibility of Integrating Art into the Homeopathic Treatment of Anxiety and Depression: An Invitation to a Scientific Comparison between Homeopathy and Art, Music and Poetry Therapy - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2025)
Our exploratory study is purely theoretical, and the development of our hypothesis for integrating homeopathy and art in the treatment of anxiety and depressive symptoms is essentially based on conceptual analysis, the interpretation of the law of similars , and the reinterpretation of artistic stimuli from a homeopathic perspective. Therefore, our investigation is not supported by experiments or clinical studies. However, to remain grounded in scientific thought, we conducted a literature search to find authoritative articles reporting the efficacy of homeopathic medicines for anxiety and depression. The efficacy of homeopathic medicines in reducing symptoms of anxiety and depression has been demonstrated through authoritative scientific research that at least partially confirms the classical homeopathic literature. With this article, taking into account the results obtained through scientific research, we wish to broaden the discussion on the possibility of including homeopathy among the therapies that can be scientifically used to treat symptoms of anxiety and depression. Furthermore, we wish to present a hypothesis developed during our exploratory, theoretical, and conceptual study regarding the possibility of using art homeopathically, consistent with the law of similars and the therapeutic action of homeopathic medicines. The reinterpretation of art from a homeopathic perspective has led us to ask the following question: can painting, sculpture, music, and poetry facilitate the therapeutic action of homeopathic medicines? We theoretically believe so, but we also recognize that a comprehensive answer to this question can only be derived from in-depth scientific research. According to our theoretical hypothesis, based on the fundamental principles of homeopathy, art can be revealed to be homeopathically curative when it acts in coherence with the law of similars and with the homeopathic method, therefore, we believe that the stimuli generated by artistic images, musical pieces and poetic verses can facilitate the action of homeopathic medicines only if they act in coherence with the fundamental principles of homeopathy, if they respect the law according to which similar cures similar , if they are able to provoke, evoke, amplify homeopathically Symptoms similar to those intended to be treated. Therapeutic intervention with art, logically, should take into account a highly personalized, comprehensive, and holistic homeopathic diagnosis, which must be matched by a targeted therapy implemented with homeopathic medicines, which today, thanks to scientific research, can be prescribed with greater clinical awareness. We encourage scientific research and hope that our theoretical and conceptual hypothesis will be confirmed in the future by high-quality studies, observations, and experiments. For now, we can theoretically conclude that certain stimuli generated homeopathically through art (painting, sculpture, music, poetry) can facilitate the action of homeopathic medicines and help alleviate or eliminate symptoms of anxiety and depression. However, in practice, we cannot provide any scientifically solid conclusions. Therefore, we hope that future scientific studies will be conducted that can provide results, information, numbers, and data that will allow us to understand the possible interactions between homeopathy and art, between artistic stimuli and pharmacological stimuli, and between artistic creations and homeopathic medicines. Scientific research has conducted interesting studies on homeopathic medicines, and although the studies are limited, in our opinion they are highly significant and provide encouraging results. These could also encourage future exploratory theoretical studies, which could lead to innovative, pioneering, and bold, yet conceptually coherent hypotheses developed with logic and rationality. We hope that our theoretical hypothesis, homeopathically pioneering and innovative yet rooted in the ancient law of similars, can provide further scientific inspiration to all researchers, including those who intend to study homeopathy in unexplored or underexplored fields, in order to understand whether the conditions exist to create a solid scientific foundation for new therapies that can be integrated with homeopathic therapy. Based on our exploratory study, the integration of art and therapy is possible, which is why we hope that future scientific research can expand, engage with, and intertwine with research on other serious therapies, such as art therapy, music therapy, and poetry therapy.